WIRELESS TRANSPORT PROTOCOL VARIANTS FOR COGNITIVE RADIO NETWORKS - Let, G Shine; Bala, G Josemin; Magdalene, W. (APTIKOM Journal on Computer Science and Information Technologies, 2018)
Scarce wireless resources, lead to development of cognitive radio network as a solution to unlicensed userscommunication in the licensed frequency band. In response to the behavior of licensed users communication, unlicensedusers communication need to change from one frequency band to another band. In this communication paradigm, theperformance of unlicensed users transmission control protocol gets degraded due to the features of cognitive radionetwork. To overcome this, several authors suggested quite a few modifications in the existing wireless transportprotocol for cognitive radio network environment. This paper gives an overview of different transport protocols usedfor unlicensed users? communication in cognitive radio networks.